Utility of Nontraditional Risk Markers in Atherosclerotic Cardiovascular Disease Risk Assessment - Yeboah, Joseph; Young, Rebekah; McClelland, Robyn L; Delaney, Joseph C; Polonsky, Tamar S; Dawood, Farah Z; Blaha, Michael J; Miedema, Michael D; Sibley, Christopher T; Carr, J Jeffrey; Burke, Gregory L; Goff, Jr, David C; et al. (Journal of the American College of Cardiology, 2016)
The improvement in discrimination gained by adding nontraditional cardiovascular risk markers cited in the 2013 American College of Cardiology/American Heart Association cholesterol guidelines to the atherosclerotic cardiovascular disease (ASCVD) risk estimator (pooled cohort equation [PCE]) is untested. This study assessed the predictive accuracy and improvement in reclassification gained by the addition of the coronary artery calcium (CAC) score, the ankle-brachial index (ABI), high-sensitivity C-reactive protein (hsCRP) levels, and family history (FH) of ASCVD to the PCE in participants of MESA (Multi-Ethnic Study of Atherosclerosis). The PCE was calibrated (cPCE) and used for this analysis. The Cox proportional hazards survival model, Harrell's C statistics, and net reclassification improvement analyses were used. ASCVD was defined as myocardial infarction, coronary heart disease-related death, or fatal or nonfatal stroke. Of 6,814 MESA participants not prescribed statins at baseline, 5,185 had complete data and were included in this analysis. Their mean age was 61 years; 53.1% were women, 9.8% had diabetes, and 13.6% were current smokers. After 10 years of follow-up, 320 (6.2%) ASCVD events occurred. CAC score, ABI, and FH were independent predictors of ASCVD events in the multivariable Cox models. CAC score modestly improved the Harrell's C statistic (0.74 vs. 0.76; p = 0.04); ABI, hsCRP levels, and FH produced no improvement in Harrell's C statistic when added to the cPCE. CAC score, ABI, and FH were independent predictors of ASCVD events. CAC score modestly improved the discriminative ability of the cPCE compared with other nontraditional risk markers.